2015
DOI: 10.1104/pp.114.256552
|View full text |Cite
|
Sign up to set email alerts
|

SENSITIVE TO PROTON RHIZOTOXICITY1, CALMODULIN BINDING TRANSCRIPTION ACTIVATOR2, and Other Transcription Factors Are Involved inALUMINUM-ACTIVATED MALATE TRANSPORTER1Expression  

Abstract: In Arabidopsis (Arabidopsis thaliana) the root apex is protected from aluminum (Al) rhizotoxicity by excretion of malate, an Al chelator, by ALUMINUM-ACTIVATED MALATE TRANSPORTER1 (AtALMT1). AtALMT1 expression is fundamentally regulated by the SENSITIVE TO PROTON RHIZOTOXICITY1 (STOP1) zinc finger protein, but other transcription factors have roles that enable Alinducible expression with a broad dynamic range. In this study, we characterized multiple cis-elements in the AtALMT1 promoter that interact with tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 46 publications
3
102
2
1
Order By: Relevance
“…2C). The first zinc finger domain of STOP1 is critical to bind to the promoter of its target genes (27). Mapping by sequencing of the lpi6 mutant revealed a 13-base pair deletion in the first exon of ALMT1 starting at position +757 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C). The first zinc finger domain of STOP1 is critical to bind to the promoter of its target genes (27). Mapping by sequencing of the lpi6 mutant revealed a 13-base pair deletion in the first exon of ALMT1 starting at position +757 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A key factor in this success is the accuracy and sensitivity of promoter prediction. Previously, we developed a unique methodology of promoter prediction using microarray data (Yamamoto et al, 2011) and used the method to identify unique promoter elements that regulate the response of a malate transporter gene, ALUMINUM-ACTIVATED MALATE TRANSPORTER1 (Tokizawa et al, 2015), to soil stresses. In this report, we utilized promoter prediction as the basis for design of synthetic promoters to identify cis-regulatory elements that can conduct environmental stress responses of ELIP2.…”
Section: Synthetic Promoter Approach To Explore Transcriptional Networkmentioning
confidence: 99%
“…Total RNA was extracted from shoots of stress-treated plants of the wild type (ecotype Columbia) and transfer DNA-tagged HY5 disruptants (SALK_096651c; Alonso et al, 2003) and subjected to real-time qRT-PCR analysis as described previously (Tokizawa et al, 2015). Primers used for RT-PCR are ELIP2_F (59-TATTGACTACACGCAACATCAGAA), ELIP2_R (59-GTTTTCTCCCTTT-GATAACTCCAT-39), UBQ1_F (59-TCGTAAGTACAATCAGGATAAGATG-39), and UBQ1_R (59-CACTGAAACAAGAAAAACAACCCT-39).…”
Section: Real-time Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study has indicated that these C 2 H 2 zinc finger domains are only responsible for directly binding to the cis-acting element GTGCCCAA in the promoter of AtALMT1, but not responsible for transcriptional activation of target genes. 23 We have examined the transcriptional activity of VuSTOP1 via a yeast expression system. Interestingly, we found that both N and C regions are responsible for transactivation.…”
Section: Structure-function Of Stop1-like Proteinsmentioning
confidence: 99%